Evaluating repellence properties of catnip essential oil against the mosquito species Aedes aegypti using a Y‑tube olfactometer - Batume, Charles; Mulongo, Ivan M.; Ludlow, Richard; Ssebaale, John; Randerson, Peter; Pickett, John A.; Mukisa, Ivan M.; Scofield, Simon (Scientific Reports, 2024)
The mosquito species Aedes aegypti (L.) is known to act as a vector in the transmission of various diseases, including dengue fever and yellow fever. The use of insect repellents is one of precautionary measures used to mitigate the risk of these diseases in humans by reducing mosquito biting. Nepetalactone, a potent natural insect repellent primarily found in catnip (Nepeta cataria) essential oil, has emerged as a promising candidate for mosquito repellence. Here, we evaluated the potential of catnip essential oil (> 95% nepetalactone) for use as a mosquito repellent. Using a Y-tube olfactometer and human hands as an attractant, we analysed the effectiveness of catnip oil at repelling the mosquito species Aedes aegypti. We tested a range of dilutions of catnip essential oil and found that concentrations as low as 2% were effective at repelling > 70% of mosquitoes for between one and four hours after repellent application. These findings suggest that nepetalactone could potentially be used as a natural, effective alternative to synthetic mosquito repellents, thereby offering protection against vector-borne diseases.